TEACHING ENGLISH INTONATION AND RHYTHM THROUGH MUSIC - Maxmanazarova Feruza Ismoilovna,; Ahmadova Rayhona Mehriddin qizi, (THE USE OF MODERN DIGITAL TECHNOLOGIES IN LINGUISTICS AND FOREIGN LANGUAGE TEACHING. INTERNATIONAL SCIENTIFIC AND PRACTICAL CONFERENCE, 2026)
This study explores how music can be used to teach English intonation and rhythm. It investigated whether incorporating songs and musical exercises into lessons helps learners improve pronunciation, stress patterns, and overall speech fluency. Data were collected through questionnaires and classroom observations from intermediate-level English learners. The findings show that learners who practiced with music spoke more naturally and fluently than those following traditional drills. Music provided a fun and engaging way to internalize the rhythm and melody of English, helping learners feel the language rather than just memorize rules. Some learners struggled with fast-paced songs, highlighting the importance of selecting materials appropriate to proficiency level. Overall, the study demonstrates that teaching English through music is effective, motivating, and practical. It offers a multisensory approach that enhances learners’ prosody, confidence, and natural speech, suggesting a promising method for language instruction